Determinação das propriedades mecânicas de compósitos de matriz epóxi reforçados com fibras de caranã - LEITE, Olívia Lopes (2022)
The use of natural fibers as reinforcement in polymeric composites has been widely studied over the years, the Amazon region stands out for harboring a high plant diversity, however still little explored scientifically. In this context, the caranã fiber stands out, as it has promising properties for engineering applications. This work seeks to characterize the caranã fiber, as well as to evaluate the efficiency in the mechanical properties of its incorporation of 10, 20 and 30% in volume in the epoxy matrix. The fiber had an average geometric density of 0.38 g/cm3, porous, circular cross-section, with a hole in the center of the section and heterogeneous longitudinal surface marked by the presence of roughness. The FTIR indicated the presence of characteristic functional groups for the fiber and revealed that the addition of fibers generates a gradual increase in the active interaction between the epoxy matrix and the molecular groups of the caranã fiber; for the tensile properties, the percentage of 30% by volume of fibers is the most effective, increasing the tensile strength by 4.5% and the stiffness by 8.8% of the composite in relation to the matrix interaction of the caranã with the epoxy matrix. The flexural properties did not show improvements from the incorporation of carana fibers in the epoxy matrix, among the mechanisms that led the material to failure are the presence of porosities and difficulty in the distribution of fibers inside the matrix.